Well-Being Status of Tribals Dependenton Shifting Cultivation in Dhalai, Tripura - Pandey, D.K.; De, H.K.; Adhiguru, P.; Pathak, Mahesh (Indian Journal of Extension Education, 2018)
This study provides an important empirical insight into well-being status of hill people of Dhalai, a remote hill district of Tripura, North Eastern Region (NER) of India whose livelihood primarily depends on Shifting Cultivation (SC). Using a resilience approach, 50 tribal households were interviewed with the help of structured interview schedule. With regard to psychological well-being, about 92% households has perceived it to be moderate or inconsistent and are experiencing difficulties as on date and is expected to continue with it in the near future. In case of economic well-being, 86%households were under poverty trap with high income inequality. Findings also revealed transition in terms of aversion of tribal youths to SC, declining dependency on SC, overdependence on Non-Timber Forest Produces, higher inclination towards settled cultivation with preferences for high value horticultural crops. Food security was found ensured among hill people and significant proportion of total expenditure was devoted on education & health.The authors suggest that the policy and political alternatives of mainstream prescriptions for hill people in Dhalaiwhich has hitherto focused on the narrow issue of shifting to settled cultivation should shift its emphasis to diversification of economic activities in the tribal regions for improving people’s well-being and natural resource management.
Keywords: Inequality; northeast India; shifting cultivation; tribal; tripura; well-being